A Computational Study on Lens Spaces Isospectral on Forms. Issue 2 (21st April 2021) - Lauret, Emilio A.
Abstract: We make a computational study to know what kind of isospectralities among lens spaces and lens orbifolds exist considering the Hodge–Laplace operators acting on smooth p -forms. Several facts evidenced by the computational results are proved and some others are conjectured.